2005
DOI: 10.1002/eji.200425727
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial inducible costimulator ligand expression is increased during human cardiac allograft rejection and regulates endothelial cell-dependent allo-activation of CD8+ T cellsin vitro

Abstract: The role of costimulatory molecules other than CD80/CD86 in endothelial cell (EC)-dependent CD8(+) T cell activation including the generation of a distinct subset of endothelium-specific CTL (EC-CTL) remains unclear. Inducible costimulator (ICOS) and its ligand (ICOSL) are new members of the CD28 family mediating effector T cell differentiation and graft rejection in animal models. In this study endothelial ICOSL expression/regulation and effects on CD8(+) T cell allo-activation were analyzed. Constitutive exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…It is important to note, however, that the role of NF-κB in ICOSL gene regulation appears to vary among different cell types. Previous studies have suggested that canonical NF-κB stimuli, such as IL-1 and TNF-α, induce the expression of ICOSL in endothelial cells and fibroblasts (35)(36)(37). Our findings suggest that LPS is inefficient in the induction of ICOSL expression in B cells.…”
Section: Discussionmentioning
confidence: 36%
“…It is important to note, however, that the role of NF-κB in ICOSL gene regulation appears to vary among different cell types. Previous studies have suggested that canonical NF-κB stimuli, such as IL-1 and TNF-α, induce the expression of ICOSL in endothelial cells and fibroblasts (35)(36)(37). Our findings suggest that LPS is inefficient in the induction of ICOSL expression in B cells.…”
Section: Discussionmentioning
confidence: 36%
“…Nonetheless, despite Tm having less of a requirement for CD80/86 and CD40 engagement, Tm may be dependent on other costimulatory pathways for the complete acquisition of effector function which may be potential targets for blockade (Table 1). For example the ICOS/ICOSL pathway has been implicated in both CD4 ϩ and CD8 ϩ memory responses (92,93). Also, 4 -1BB/4 -1BBL interactions have been shown to be important in CD8 ϩ T-cell recall responses (94,95) and it has been suggested that there may be a significant contribution of OX40/OX40L interactions in memory CD4 ϩ T-cell responses (95,96).…”
Section: Strategies To Inhibit Memory T-cell Responses To An Allograftmentioning
confidence: 97%
“…ICOS provides a positive signal to T cells by binding to its ligand (ICOS-L) on professional antigen-presenting cells (APCs) such as B cells, macrophages and dendritic cells (DCs) [14], as well as other cell types, including endothelial [15] and epithelial [16] cells. Initially, ICOS was shown to enhance the proliferation and differentiation of T cells via the induction of certain cytokines such as IL-4 [17], IL-5, interferon (IFN)-g and IL-10 [13].…”
Section: Introductionmentioning
confidence: 99%